Radial growth and activity of antioxidant enzymes in the three post-radiation Cladosporium cladosporioides generations - A. V. Tugay; T. I. Tugay; V. A. Zheltonozhsky; M. V. Zheltonozhskaya; L. V. Sadovnikov; G. V. Ponomarenko; О. B. Polischuk (Ядерна фізика та енергетика)
Radial growth rate and activity of antioxidant enzymes - superoxide dismutase (SOD), catalase and peroxidase - in three post-radiation generations of two strains of Cladosporium cladosporioides: control and with radioadaptive properties were investigated. It was established that hormesis effect by the increase rate of radial growth is more pronounced in post-radiation generations of the control strain than in the generations of strain with radioadaptive properties. However, in enzymatic antioxidant defense system significant hormesis effect is revealed only in three post-radiation generations’ strain with radioadaptive properties, which appears in the increase up to 2 times in SOD activity and the peroxidase activity up to 4 times.